Development of a robotic weed control system for greenhouses - Heravi, Amid (2018)
In this study, a robot prototype that moves on a monorail was designed and developed using analytical and experimental methods. It’s purpose was weed elimination between cucumber plants inside the greenhouse plants since there is not much research done for a robotic weed control in a cucumber greenhouse. The plants are cultivated in one row and the distance between two plants is about 40 cm. The distance between two rows is almost 1 meter. The soil type of the cucumber greenhouse was sandy loam soil. The robot benefits from 3 arrays of ultrasonic sensors for weed detection and a PIC18 F4550-E/P microcontroller board for processing. The feedback from the sensors activates a robotic arm which moves inside the rows of the cucumber plants for cutting the weeds using rotating blades. Fifty four experiments were carried out inside a greenhouse to find the best combination of arm motor (AM) speed, blade rotation (BR) speed, and blade design. Three BR speeds of 3500, 2500 and 1500 rpm were assigned. The selection of the BR speeds was based on the previously published results on rotary movers, and two AM speed of 10 and 30 rpm to three blade designs of S-shaped, triangular-shaped, and circular-shaped. These blades were selected due to their availability, low cost, and their performance during the initial test experiments.